2022
DOI: 10.3389/fevo.2022.826808
|View full text |Cite
|
Sign up to set email alerts
|

Satellitome of the Red Palm Weevil, Rhynchophorus ferrugineus (Coleoptera: Curculionidae), the Most Diverse Among Insects

Abstract: The red palm weevil, Rhynchophorus ferrugineus, is the most harmful species among those pests affecting palm trees. Its impact causes important economic losses around the World. Nevertheless, the genetic information of Rh. ferrugineus is very scarce. Last year, the first genome assembly was published including a rough description of its repeatome. However, no information has been added about one of the main components of repeated DNA, the satellite DNA. Herein, we presented the characterization of the satellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…Its satellitome builds 25% of the genome, and abundant families were found to be dominantly deposited in euchromatin, although they are also distributed in the pericentromeric heterochromatin of all chromosomes or on specific chromosomes only. Interestingly, the copy number of some satDNA families is increased in populations that invaded new habitats most recently [ 114 ].…”
Section: In and Out Of Heterochromatinmentioning
confidence: 99%
“…Its satellitome builds 25% of the genome, and abundant families were found to be dominantly deposited in euchromatin, although they are also distributed in the pericentromeric heterochromatin of all chromosomes or on specific chromosomes only. Interestingly, the copy number of some satDNA families is increased in populations that invaded new habitats most recently [ 114 ].…”
Section: In and Out Of Heterochromatinmentioning
confidence: 99%
“…The study of repeats in the RPW genome is in its infancy, but the use of genomics has greatly accelerated its progress. In the past year, two studies were published using short-read sequencing to characterize microsatellites and satDNAs in the RPW [ 72 , 87 ]. Manee et al [ 72 ] generated a new low-coverage draft genome of the adult female RPW to search for microsatellite content (1–6 bp long) and compare it to other beetles from the Curculionidae family, including the two publicly available draft genomes of the RPW [ 72 ].…”
Section: Omics Technologies and Their Impact On Pest Sciencementioning
confidence: 99%
“…Montiel et al [ 87 ] carried out the first attempt to characterize satDNAs of the RPW genome [ 87 ]. These authors found 121 satDNA families in the RPW, comprising 25% of its genome, the highest diversity of satDNA families of any insect to date.…”
Section: Omics Technologies and Their Impact On Pest Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Variable occurrence of satellite DNA in different strains and isolates of the parasitic flatworm Schistosoma mansoni also points to the possible mobile nature of the satellite, affecting genetic variability and might be important for the evolution and biology of the species [ 91 ]. Satellite DNAs are known to be subjected to a high evolutionary turnover, resulting in not only a rapid copy number change [ 92 , 93 , 94 ], but also the emergence of new satellites [ 95 ]. One such example is the newly amplified satellite DNA in the New World Monkey genus Aotus , which enables night vision [ 96 ].…”
Section: Satellite Dna and Environmental Adaptationmentioning
confidence: 99%